2019
DOI: 10.1021/acs.energyfuels.9b03269
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal Thermogravimetric Kinetic Investigations on Combustion Behaviors of Concomitant Biomass from Urban Plants

Abstract: Thermogravimetric combustion characteristics of white poplar leaves, pine needles, poplar leaves, ginkgo leaves, and corn straw in air were tested under different heating rates. The results indicated that the combustion process of biomass consisted of at least two independent reactions, while the number of reactions was related to the properties of components in biomasses. In addition, the corresponding temperature of the maximum reaction rate on reaction rate curves shifted into higher temperature zones with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The peak temperature of the sample increased with the increase of the heating rate, which was common in nonisothermal heating, mainly due to the thermal lag phenomenon. 8,23 At a low heating rate, the temperature gradient between the particles was small, and the temperature difference between the inside and the outside of the particles was small, 24 forming a good heat transfer from the surface to the inside. On the contrary, at a high heating rate, a relatively higher temperature gradient made the temperature difference between the inside and outside of the particles larger, resulting in a lag in the reaction.…”
Section: Kinetics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The peak temperature of the sample increased with the increase of the heating rate, which was common in nonisothermal heating, mainly due to the thermal lag phenomenon. 8,23 At a low heating rate, the temperature gradient between the particles was small, and the temperature difference between the inside and the outside of the particles was small, 24 forming a good heat transfer from the surface to the inside. On the contrary, at a high heating rate, a relatively higher temperature gradient made the temperature difference between the inside and outside of the particles larger, resulting in a lag in the reaction.…”
Section: Kinetics Analysismentioning
confidence: 99%
“…Thermogravimetry analysis (TGA) was used to study the combustion process of MSW, which was helpful to analyze the combustion mechanism and obtain the kinetic parameters. , The components of MSW and the heating rate were the main factors affecting the combustion process and product properties of MSW . The main thermal reaction temperature of MSW components was concentrated in the range of 150–500 °C, but the thermal stability properties of different components were quite different. According to TG analysis of typical components, it was found that food residue presented multiple peaks below 320 °C, printing paper presented the main peak at 350 °C, and polyethylene (PE) and polypropylene (PP) presented a very strong peak at 455 to 485 °C . In addition, the ignition difficulty of MSW components was ranked in the order of kitchen waste < wood, bamboo < paper < fabric < plastic.…”
Section: Introductionmentioning
confidence: 99%